2021
DOI: 10.12911/22998993/135775
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Use of Artificial Neural Networks for Modeling the Rainfall–Runoff Relationship in Water Resources Management

Abstract: Recently, Artificial Neural Network (ANN) methods, which have been successfully applied in many fields, have been considered for a large number of reliable streamflow estimation and modeling studies for the design and project planning of hydraulic structures. The present study aimed to model the rainfall-runoff relationship using different ANN methods. The Nergizlik Dam, located in the Seyhan sub-basin and one of the important basins in Turkey, was chosen as the study area. Analyses were carried out based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…The weights are modified after each iteration of the training set until the total error is below a predefined tolerance. A feedforward neural network with backpropagation is one of several neural network architectures that have been extensively employed in hydrological modeling (Tikhamarine et al, 2020; Turhan, 2021). Hence, a three‐layer neural network with backpropagation was used for streamflow modeling in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The weights are modified after each iteration of the training set until the total error is below a predefined tolerance. A feedforward neural network with backpropagation is one of several neural network architectures that have been extensively employed in hydrological modeling (Tikhamarine et al, 2020; Turhan, 2021). Hence, a three‐layer neural network with backpropagation was used for streamflow modeling in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Ortalama yıllık akış 211 m 3 /s dolaylarındadır (Özfidaner ve ark., 2018). Seyhan Havzası'nda yer yer Akdeniz iklimi ve karasal iklim özellikleri görülebilmektedir (Turhan, 2021). Seyhan Nehri ana su kaynağı olup, ana kollarını Göksu ve Zamantı Nehirleri oluşturmaktadır (Selek ve ark., 2016;Turhan, 2022).…”
Section: çAlışma Alanı Ve Gözlem Verileriunclassified
“…The findings demonstrated that the ANN technique offered a viable and viable substitute to conceptual models for simulations and forecasting in watershed modeling. Numerous investigations utilized the ANN for rainfall-runoff modeling, which is recognized as a black box technique (Roy & Singh 2020;Turhan 2021). The adaptive-network-based fuzzy inference system (ANFIS) model combines the inference process of fuzzy mathematics with the connectionist capability of ANN and has been applied for rainfall-runoff modeling for the past two decades .…”
Section: Introductionmentioning
confidence: 99%